2021
DOI: 10.1177/1129729821989904
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of tunneled cuffed hemodialysis catheters: An experience from a tertiary care center in Karachi, Pakistan

Abstract: Introduction: Tunneled cuffed catheters (TCC) are generally used as a temporary means to provide hemodialysis (HD) until permanent arteriovenous access is established. However, certain complications are associated with use of TCCs such as infections, catheter malfunction/malposition or venous stenosis. Limited data is available on outcomes and long term complications associated with TCCs in our country. The aim of this study was to study the outcomes of TCCs and associated long term complications during the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…The median catheter stay was reported to be 62.5 (IQR: 46-89.5) days in a study from Pakistan. 15 A median catheter usage of 213 days was observed by Sampathkumar et al 16 Yalvac et al report a catheter use mean duration of 729.65 days. 17 A study in Egypt found that the average catheter lasted 122 days.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The median catheter stay was reported to be 62.5 (IQR: 46-89.5) days in a study from Pakistan. 15 A median catheter usage of 213 days was observed by Sampathkumar et al 16 Yalvac et al report a catheter use mean duration of 729.65 days. 17 A study in Egypt found that the average catheter lasted 122 days.…”
Section: Discussionmentioning
confidence: 94%
“…Another similar investigation from Pakistan found that during the observation period, 19.8% patients experienced CRBSIs, and 63.6% of these patients required catheter removal. 15 During one-year follow-up, bacteraemia risk was reported to be 9% at one year and any central venous catheter (CVC)related complication risk to be 30%. 19 In contrast to current findings, an upsetting infection rate was reported by an Indian study, showing that during a six-month follow-up period following the installation of the TDC, 30.4% patients had positive blood cultures.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, during one year period total 8.5% developed CRBSI which yielded an incidence rate of 5.01 per 10,000 catheter days. Another Pakistani study reported that 19.8% of patients developed CRBSI during the study period and catheter removal was required in 63.6% of these patients [20]. A risk of 9% at one year was reported for bacteremia and 30% for any CVC related complication during rst year follow-up [27].…”
Section: Discussionmentioning
confidence: 98%
“…The mean duration of catheter use greatly varies among studies. Another Pakistani study reports a median catheter duration of 62.5 (IQR=46 -89.5) days [20]. Sampathkumar et al reported a median catheter usage of 213 days [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation